The genetic structure of native Americans in North America based on the Globalfiler® STRs. (November 2016) - McCulloh, Kelly L.; Ng, Jillian; Oldt, Robert F.; Weise, Jessica A.; Viray, Joy; Budowle, Bruce; Glenn Smith, David; Kanthaswamy, Sreetharan
Highlights: Globalfiler® markers were used to analyze ten North American tribes. Allele frequency, heterozygosity, and F-statistics data were generated. An FST or θ value of 0.04 was estimated among these tribes. This estimate is more than above the conservative 0.03 recommended by the NRC. Data show reliable population genetic estimates necessitate additional tribal samples. Abstract: Current forensic STR databases, such as CODIS, lack population genetic data on Native American populations. Information from a geographically diverse array of tribes is necessary to provide improved statistical estimates of the strength of associations with DNA evidence. The Globalfiler® STR markers were used to characterize the genetic structure of ten tribal populations from seven geographic regions in North America, including those not presently represented in forensic databases. Samples from the Arctic region, Baja California, California/Great Basin, the Southeast, Mexico, the Midwest, and the Southwest were analyzed for allele frequencies, observed and expected heterozygosities, and F-statistics. The tribal samples exhibited an FST or θ value above the conservative 0.03 estimate recommended by the National Research Council (NRC) for calculating random match probabilities among Native Americans. The greater differentiation among tribal populations computed here (θ = 0.04) warrants the inclusion of additional regional Native American samples into STR databases.